Normocalcemic primary hyperparathyroidism is an early stage of primary hyperparathyroidism according to fibroblast growth factor 23 level - Chertok Shacham, Elena; Maman, Nimra; Lazareva, Tatyana; Masalha, Refaat; Mahagna, Lila; Sela, Gala; Ishay, Avraham (Frontiers in Endocrinology, 2023)
Introduction Normocalcemic primary hyperparathyroidism is a variant of primary hyperparathyroidism with consistently normal albumin-adjusted or free-ionized calcium levels. It may be an early stage of classic primary hyperparathyroidism or could represent primary kidney or bone disorder characterized by permanent elevation of PTH level. Aim of the study The study aims to compare the FGF-23 levels in patients with PHPT, NPHPT, and normal calcium and PTH levels. Methods Our study included patients who were referred to the endocrinology clinic with a presumptive diagnosis of primary hyperparathyroidism, an isolated increased level of PTH, or reduced bone densitometry. For each patient, we performed blood analysis of FGF-23, calcium, phosphate, vitamin D [25(OH)D3], estimated glomerular filtration rate (eGFR), bone turnover markers, and urine analysis for calcium/creatinine ratio. Results Our study included 105 patients. Thirty patients with hypercalcemic hyperparathyroidism (HPHPT group), thirty patients with elevated PTH and normal calcium levels (NPHPT group), and 45 patients with normal calcium and PTH levels in the control group. FGF 23 level was 59.5± 23 pg/ml in the NPHPT group, 77±33 pg/ml in the HPHPT group, and 49.7±21.7 pg/ml in the control group (p=0.012). The phosphate level was lowest in the HPHPT group: 2.9 ±0.6 vs 3.5±0.44 in the NPHPT and 3.8±0.5 in the control groups (p=0.001). No differences were found in eGFR, 25(OH)D3, C-terminal telopeptide type I collagen (CTX) and procollagen type 1 N-terminal propeptide (P1NP) levels, and bone densitometry scores between the three study groups. Conclusion. Our findings suggest that NPHPT is an early stage of PHPT. Further studies are needed to determine the role of FGF-23 and its usefulness in NPHPT.